Impact of Cathode Materials, Thickness, and Charging C-rate on Lithium Deposition in Lithium-Ion Batteries - Chang, Zhen (My University, 2025)
Abstract Lithium-ion batteries (LIBs) are widely used in modern energy storage systems due to their high energy density, long cycle life, and fast charging capability. However, lithium plating during high-rate charging remains a critical challenge, leading to capacity degradation, impedance rise, and safety risks such as internal short circuits and thermal runaway. This thesis investigates how cathode material properties, electrode thickness, and charging protocols collectively influence lithium plating and capacity loss in coin cells paired with lithium metal-based anodes. Three cathode chemistries are examined: NMC811 (Nickel Manganese Cobalt), LFP (Lithium Iron Phosphate), and LFMP (Lithium Manganese Iron Phosphate). Galvanostatic cycling was performed under stepwise increasing C-rates (0.1C, 1C, 2C) to evaluate capacity retention and CE behavior. Electrochemical Impedance Spectroscopy (EIS) was conducted after all cycling was completed, to assess the cumulative development of internal resistance and interfacial degradation. The results show that cathode composition significantly affects interfacial stability. NMC811 exhibits the highest initial capacity but suffers from rapid impedance growth at high rates. LFP shows superior cycling stability and minimal impedance change, while LFMP offers intermediate performance but is sensitive to abrupt fast charging. Thicker electrodes tend to accelerate capacity fade due to transport limitations, whereas thinner ones provide more stable cycling behavior. Moreover, stepwise charging protocols improve efficiency across all systems, particularly mitigating degradation in LFMP cells. Overall, this work provides insights into the interplay between material selection, electrode design, and fast-charging strategies, offering guidance for improving the performance and reliability of lithium-ion batteries in high-rate applications.
Keywords: Keywords: Lithium plating, Electrode thickness, Fast charging, Lithium-ion battery, Impedance spectroscopy